RNA silencing proteins and small RNAs in oomycete plant pathogens and biocontrol agents - Piombo, Edoardo; Kelbessa, Bekele Gelena; Sundararajan, Poorva; Whisson, Stephen C.; Vetukuri, Ramesh Raju; Dubey, Mukesh (Frontiers in Microbiology, 2023)
Oomycetes cause several most damaging diseases of plants and animals, and some species also act as biocontrol agents on insects, fungi, and other oomycetes. RNA silencing is increasingly being shown to play a role in the pathogenicity of Phytophthora species, either through trans-boundary movement of small RNAs (sRNAs) or through expression regulation of infection promoting effectors. To gain a wider understanding of RNA silencing in oomycete species with more diverse hosts, we mined genome assemblies for Dicer-like (DCL), Argonaute (AGO), and RNA dependent RNA polymerase (RDRP) proteins from Phytophthora plurivora, Ph. cactorum, Ph. colocasiae, Pythium oligandrum, Py. periplocum, and Lagenidium giganteum. Each of the species possessed a single DCL protein, but more diversity in numbers and sequences of AGOs and RDRPs were found. Sequencing of sRNA populations from cultured mycelium of each species revealed prevalence of 21nt, 25nt, and 26nt sizes in all oomycetes analyzed, but the relative abundance and 5’ base preference of these size classes differed markedly between genera. The majority of sRNAs mapped to transposons and other repeats, signifying that the major role for RNA silencing in oomycetes is to limit the expansion of these elements. We also found that sRNAs may act to regulate the expression of duplicated genes. Other sRNAs mapped to several gene families, and this number was higher in Pythium spp., suggesting a role of RNA silencing in the regulation of gene expression. Genes for most effector classes were the source of sRNAs of variable size, but in some cases single gene families showed a preference for specific classes of sRNAs, such as 25/26 nt sRNAs targeting RxLR effector genes in Phytophthora species. Novel microRNAs were discovered from all species, and two were predicted to act on transcripts for RxLR effectors in Ph. plurivora and Ph. cactorum, indicating a putative role in regulating infection. Moreover, microRNAs from the biocontrol Pythium species had sequence matches in the predicted transcriptome of Phytophthora infestans and Botrytis cinerea, and L. giganteum miRNAs matched candidate genes in the mosquito Aedes aegypti. This suggests that trans-boundary RNA silencing may have a role in the biocontrol action of these oomycetes.